Screening of Different Physalis Genotypes as Potential Rootstocks or Parents Against Vascular Wilt Using Physiological Markers - Cháves-Gómez, Jose Luis; Becerra-Mutis, Laura Marcela; Chávez-Arias, Cristhian Camilo; Restrepo-Díaz, Hermann; Gómez-Caro, Sandra (Frontiers in Plant Science, 2020)
Cape gooseberry (Physalis peruviana L.) is one of the most exported Andean fruits in Colombia. Vascular wilt caused by Fusarium oxysporum f. sp. physali (FOph) has led to a reduction in crop areas in recent years. Therefore, the aim of this study was to select genotypes with resistance to vascular wilt that can be useful as rootstocks from a group of six Physalis genotypes (Physalis ixocarpa, Physalis floridana, and Physalis peruviana genotypes Colombia, Sudafrica, Peru and Accession 62) using physiological variables such as maximum quantum efficiency of Photosystem II (Fv/Fm), leaf gas exchange properties (net photosynthesis rate (Pn) and stomatal conductance (gs)) and leaf water potential. An experiment was carried out under greenhouse conditions in which plants of the different Physalis materials were inoculated with the F. oxysporum f. sp. physali strain Map5 at a concentration of 1 x 106 conidia mL-1. Physiological and disease development variables were measured at 15, 23 and 31 days after inoculation (DAI). The results obtained showed that P. peruviana genotypes Colombia and Sudafrica showed greater susceptibility to the disease (disease severity index 3.8 and 3.6, respectively). Net photosynthesis rate (Pn), stomatal conductance (gs), water potential (Ψfw), and Fv/Fm ratio were lower compared to non-inoculated plants. P. floridana and P. ixocarpa plants inoculated with F. oxysporum showed similar behavior to non-inoculated plants for the evaluated variables. In conclusion, the results obtained suggest that these two genotypes can be considered in breeding programs or as rootstock for the establishment of cape gooseberry crops in soils with the presence of the pathogen.